The Transformation of Islamic Values in the Wiwitan Harvest Tradition: An Islamic Education Sociology Perspective - Nabila Amalia; Nafiatur Rosyida; Maskuri (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
Abstract The rapid transformation of local cultural traditions in the modern era has raised concerns regarding the preservation of indigenous values and their integration with Islamic teachings. As one of the agrarian traditions maintained by Javanese Muslim communities, the Wiwitan harvest thanksgiving tradition reflects the acculturation between local culture and Islamic educational values in social life. This study aims to explore the implementation of the Wiwitan tradition, identify the Islamic values embedded within it, and analyze the internalization of Islamic educational values through the harvest thanksgiving tradition in Sumberejo. This research employed a qualitative method with an ethnographic approach. Data were collected through observation, interviews, and documentation, and analyzed descriptively to understand the socio-religious meaning of the tradition. The findings reveal that the Wiwitan tradition practiced by the community has undergone a process of Islamization in line with the dominance of Islamic orthodoxy in Javanese society. The tradition embodies both divine values (ilahiyyah) and humanistic values (insaniyyah), including gratitude, charity, kinship, and tolerance. The internalization of Islamic educational values is carried out through the stages of projection, introspection, identification, habituation, reflection, and value evaluation. These findings indicate that the Wiwitan tradition functions not only as a cultural ritual but also as a medium for strengthening Islamic educational values and social harmony within the community.